2006
DOI: 10.1200/jco.2005.05.4684
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of CHOP Plus Rituximab in Patients With HIV-Associated Non-Hodgkin's Lymphoma

Abstract: Rituximab adjunction to CHOP produced a CR rate of 77% and a 2-year survival rate of 75% in patients with AIDS-related non-Hodgkin's lymphoma, without increasing the risk of life-threatening infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
95
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(115 citation statements)
references
References 17 publications
12
95
1
7
Order By: Relevance
“…However, this study did not have the power to show a significant difference and the follow-up is extremely short. In another phase II study, R-CHOP produced a CR rate of 77% and a 2-year survival rate of 75% without severe infectious complications (Boue et al, 2006).…”
Section: Other Lymphomasmentioning
confidence: 96%
“…However, this study did not have the power to show a significant difference and the follow-up is extremely short. In another phase II study, R-CHOP produced a CR rate of 77% and a 2-year survival rate of 75% without severe infectious complications (Boue et al, 2006).…”
Section: Other Lymphomasmentioning
confidence: 96%
“…Therefore, the liposomal cytarabine schedule was different according to the systemic chemotherapeutic regimens used. Patients with CD20-positive diffuse large B-cell lymphoma (DLBCL) received CHOP (cyclophosphamide, hydroxydaunomycin, Oncovin, prednisone) with rituximab (R-CHOP) 34 or rituximab plus infusional cyclophosphamide, doxorubicin, and etoposide (R-CDE) 35 every 3 weeks; patients with plasmablastic lymphoma or primary effusion lymphoma (PEL) received the standard CHOP, 36 and patients with Burkitt subtype received the rituximab plus cyclophosphamide, oncovin, hydroxydaunomycin, high-dose methotrexate, ifosphamide, etoposide, high-dose cytarabine (R-CODOX-M/IVAC) regimen 37 or the Stanford regimen for Burkitt. 38 Liposomal cytarabine was administered every 3 weeks in patients who received R-CHOP, CHOP, or R-CDE up to 6 cycles and on Day 1 of R-CODOX-M up to 3 cycles or on Day 1 of the Stanford regimen up to 6 cycles.…”
Section: Treatmentmentioning
confidence: 99%
“…Moreover, comparing our schedule with that previously used with methotrexate or cytarabine in the most important published studies, a significant reduction of intrathecal injection occurred with comparable side effects. 19,21,[34][35][36][37][38]52 These data are reported in Table 3. This is an important matter both for patients and physicians.…”
mentioning
confidence: 99%
“…Several clinical trials (17)(18)(19)(20)(21) and observational studies (22)(23)(24) with HIV-infected lymphoma cases treated with HAART reported survival outcomes comparable to general patients with lymphoma. However, a few studies directly compared HIV-infected and HIV-uninfected patients with lymphoma and found inconsistent results.…”
Section: Introductionmentioning
confidence: 99%